The impact of drought-induced root and root hair shrinkage on root–soil contact - Duddek, Patrick; Carminati, Andrea; Koebernick, Nicolai; Ohmann, Luise; Lovric, Goran; Delzon, Sylvain; Rodriguez-Dominguez, Celia M; King, Andrew; Ahmed, Mutez Ali (Plant physiology (Bethesda), 2022)
Although root hairs significantly increased root–soil contact, in maize, their shrinkage during soil drying is initiated at relatively high soil matric potentials (between −10 and −310 kPa).